2006
DOI: 10.3177/jnsv.52.223
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Apolipoprotein B Secretion from HepG2 Cells by Glucosyl Hesperidin

Abstract: SummaryOur previous study has shown that a soluble hesperidin derivative, glucosyl hesperidin (G-hesperidin), preferentially lowers serum triglyceride (TG) level in hypertriglyceridemic subjects through the improvement of very low-density lipoprotein (VLDL) metabolic abnormality. G-Hesperidin has also been found to decrease an elevated serum apolipoprotein B (apo B) level in the hypertriglyceridemic subjects, suggesting a possibility that this compound suppresses excess VLDL secretion in the liver. In the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 38 publications
0
13
3
Order By: Relevance
“…In such experimental conditions, a plasma TG‐lowering effect has been shown to be exerted by increasing TG clearance but not by inhibiting lipogenesis in the liver (Murosaki et al ., ). Therefore, effects of G‐hesperidin alone or G‐hesperidin + caffeine, which could suppress VLDL secretion from the liver (Miwa et al ., ), on plasma TG levels may not appear in the present study.…”
Section: Discussioncontrasting
confidence: 69%
See 2 more Smart Citations
“…In such experimental conditions, a plasma TG‐lowering effect has been shown to be exerted by increasing TG clearance but not by inhibiting lipogenesis in the liver (Murosaki et al ., ). Therefore, effects of G‐hesperidin alone or G‐hesperidin + caffeine, which could suppress VLDL secretion from the liver (Miwa et al ., ), on plasma TG levels may not appear in the present study.…”
Section: Discussioncontrasting
confidence: 69%
“…In such experimental conditions, a plasma TG-lowering effect has been shown to be exerted by increasing TG clearance but not by inhibiting lipogenesis in the liver (Murosaki et al, 2007). Therefore, effects of G-hesperidin alone or G-hesperidin + caffeine, which could suppress VLDL secretion from the liver (Miwa et al, 2006), on plasma TG levels may not appear in the present study. DNA microarray analysis revealed that apoAI and apoAII were markedly decreased in epididymal adipose tissue in obese KK mice fed a low-fat diet that included G-hesperidin + caffeine (Table 4).…”
mentioning
confidence: 68%
See 1 more Smart Citation
“…f.) have been reported to be such flavanone glycosides as eriocitrin (eriodictyol 7- O -β-rutinoside) and hesperidin (hesperetin 7- O -β-rutinoside), naringin (naringenine-7-rhamnosidoglucoside), and such flanone glycosides as diosmin (diosmetin 7- O -β-rutinoside) and 6,8 C-diglucosyldiosmetin [ 9 , 10 ], all of which are supposed to have a number of positive health effects in the prevention of lifestyle-related diseases, and to have antiinflammatory, anticancer, and antiviral activities based on their antioxidant activity [ 11 14 ]. Furthermore, previous studies demonstrated the effects of these flavonoids on lipid and glucose metabolism in experimental animals and humans [ 15 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…G-hesperidin has been reported to reduce serum levels of triglyceride (TG) in animals [ 13 – 15 ] and subjects with hypertriglyceridemia [ 16 , 17 ]. The mechanism of the TG-lowering effect of G-hesperidin is thought to be down-regulation of the synthesis/secretion of very-low-density lipoprotein in hepatocytes [ 18 ], inhibition of lipogenesis, and induction of beta oxidation of fatty acids in high-fat diet-fed rats [ 15 ]. Studies have shown that daily intake of G-hesperidin (500 mg) in subjects with a moderately high BMI for 12 weeks decreases abdominal fat significantly during the period, but these decreases do not differ significantly from those of subjects taking a placebo [ 19 ].…”
Section: Introductionmentioning
confidence: 99%